2017
DOI: 10.1002/jcp.25721
|View full text |Cite
|
Sign up to set email alerts
|

Generation of Insulin‐Producing Cells From Human‐Induced Pluripotent Stem Cells Using a Stepwise Differentiation Protocol Optimized With Platelet‐Rich Plasma

Abstract: Studies on patient-specific human-induced pluripotent stem cells (hiPSCs) as well as a series of autologous growth factors presumably will reveal their many benefits for cell base replacement therapy in type 1 diabetes mellitus (TIDM) patients in the future. For this purpose, we established a multistep protocol by adding platelet-rich plasma (PRP) that induce the hiPSCs into insulin-producing cells (IPCs). We present here a differentiation protocol consisting of five stages in two groups including protocol wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
41
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 48 publications
(46 citation statements)
references
References 37 publications
4
41
0
Order By: Relevance
“…However, the results of this study indicated that the Glut‐2 gene was expressed in both experimental groups, but, the difference between the two experimental groups was not statistically significant. This result aligned with Enderami et al (). For this reason, the result (Figures a and b) showed that the difference of C‐peptide and insulin releasing in response to the low level of glucose (5.5 mM) concentration between the two experimental groups was not significant.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…However, the results of this study indicated that the Glut‐2 gene was expressed in both experimental groups, but, the difference between the two experimental groups was not statistically significant. This result aligned with Enderami et al (). For this reason, the result (Figures a and b) showed that the difference of C‐peptide and insulin releasing in response to the low level of glucose (5.5 mM) concentration between the two experimental groups was not significant.…”
Section: Discussionsupporting
confidence: 92%
“…In the present study, insulin secretion in response the high level of glucose stimulation of IPCs on the PVA scaffold was significantly higher than the 2D culture system. In this study, the observed results of pancreatic specific markers expression in mRNA and protein level assessment were aligned with the other studies in the field of stem cell differentiation to IPCs (Enderami et al, ; Khorsandi et al, ; Zhang et al, ). One of the advantages of 3D culture system in the long process of differentiation is increasing cell proliferation and viability compared with the 2D culture.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…[44][45][46] Consistent with these reports, our cell cycle assay also showed that the majority of undifferentiated hiPSCs were in the proliferation phase (S phase), however, after treatment with activin A, as an specification inducing signal, the majority of hiPSCs cultured in both TCP and DWJS were entered in the G0/G1 phase, with the cells cultured on DWJS having more G0/G1 positive cells. These reports demonstrated that pluripotent stem cells have a short G0/G1 phase; however, when these cells are exposed to specification cues, their developmental programs are activated and their cell cycle remodels, so that the length of G1 phase increase.…”
Section: Discussionsupporting
confidence: 89%